Removal of Toluene From Indoor Air Under Optimal Conditions Using Ficus elastica Roxb. Plants Obtained by Micropropagation - Buran, Abayhan; Topdemir, Aykut (Wiley, 2026)
This study optimized the removal efficiency of toluene from a botanical air filtration system created using the Ficus elastica plant by utilizing compound concentration, relative humidity, and time variables. Experiments were conducted to establish optimal conditions using micropropagated plants. Additionally, the possible desorption concentration after removal and any changes that may occur in the plant due to VOC exposure throughout this process were investigated. Response surface methodology (RSM) optimization results showed that over 90% VOC removal efficiency can be achieved for the F. elastica and toluene compound. Under optimal conditions, the maximum removal efficiency for toluene was 92.01%. In tests on micropropagated new plants, an increase in removal efficiency was observed as the number of tests increased, proportional to the frequency of exposure to volatile organic compounds. It was observed that prolonged exposure caused an increase in antioxidant compounds, which are a stress response in plants, a decrease in chlorophyll content, and tissue damage in stoma structures. In conclusion, botanical filtration systems can remove VOCs at high efficiency levels, which can be further increased through optimization efforts. Botanical filtration plays a significant role in the development of economical, efficient, and sustainable systems for components in indoor air that pose a threat to human health.
Keywords: botanical filtration; Ficus elastica; RSM; toluene; VOC removal